Assessment of the risk of QT-interval prolongation associated with potential drug-drug interactions in patients admitted to Intensive Care Units - Flávia Medeiros Fernandes; Aryelle Mayara da Silva Paulino; Bruna Camelo Sedda; Eliane Pereira da Silva; Rand Randall Martins; Antonio Gouveia Oliveira (Elsevier, 2019)
Objectives: To evaluate the relationship between drug interactions and QT-interval prolongation in patients admitted to a general intensive care unit (ICU). Methods: This study was approved by the Institutional Review Board and written informed consent was obtained from all patients. From May 2015 to July 2016, all patients over 18 years-old admitted to the ICU for more than 24 h and in whom the QT-interval on the ECG could be read were prospectively included in this observational, cross-sectional study. All medications administered in the 24 h prior to admission were recorded and the QT-interval was measured upon ICU admission and corrected with Bazzet's formula (QTc). Drug-drug interactions involving drugs potentially associated with QTc prolongation (DDIQT) were searched and QTc increase associated with pharmacokinetic (PK-DDIQT) and pharmacodynamic (PD-DDIQT) interactions was assessed with multiple regression adjusted by patient varibles. Results: The study population consisted of 283 patients, 54.4% males, mean age 57.6 ± 16.7 years-old. Forty five (15.9%) patients presented 65 DDIQT with predominance of pharmacodynamic (66.1%). The risk of DDIQT prescription increased with lower systolic blood pressure, in hypokalemia, in non-diabetics and with the number of medications. PK-DDIQT alone did not affect the QTc interval (7.75 ms, 95%CI: -22.4 to 37.9 ms, p = 0.61), but PD-DDIQT increased QTc by 28.4 ms (95%CI: 9.67 to 47.4 ms, p = 0.003). Most PD-DDIQT involved metoclopramide with ondansetron or amiodarone, and ondansetron with ciprofloxacin. Conclusions: In patients exposed to drugs associated with prolonged QTc in the 24 h prior to ICU admission, pharmacodynamic DDIQT are associated with increased risk of QTc prolongation. Keywords: Arrythmias, Cardiac, Drug interactions, Drug prescriptions, Intensive Care Units, Long QT syndrome, Torsades de pointes